On the road to Weimar? The political economy of popular satisfaction with government and regime performance in Germany - Thomas R. Cusack (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1997)
The focus of this paper is on citizens' satisfaction with the German democratic political system. This paper presents an argument to the effect that the performance records of both the economy and the government in power have substantial impacts on the levels of popular satisfaction with the regime. This theoretical stance contradicts the cultural vision of democratic stability and its thesis that political culture, with its inertial qualities, provides stable moorings for a political system. The results presented here suggest that Reunification has taken its toll on the German political system. In the New Federal States satisfaction with the Federal Republic's political system remains very low and this dissatisfaction has spread into West Germany. Public satisfaction with the system in the West has sunk to its lowest level since data have been collected on this phenomenon. The sources of this are to be seen in both economic developments and government performance. Contrary to the culturalist vision of the Federal Republic's democracy, satisfaction with the political system in Western Germany is not a given; citizens modify their views on the system in light of both the government's and the economy's successes and failures. The dynamic is similar in the East. The economic strains of Reunification and the perception that the federal government is not making sufficient efforts to bring East German living standards up to those of the West have kept the population there from committing themselves to the system. While most East Germans now admit that it was not a mistake to have merged with the Federal Republic and accept its political model, little enthusiasm exists for that model or for the economic system linked to it. – – Im Mittelpunkt dieses discussion papers steht die Zufriedenheit der Bundesbürger mit dem bestehenden deutschen demokratischen System. Die Argumentation zielt darauf ab, daß sowohl die Leistungsfähigkeit der Wirtschaft wie der Regierung das Ausmaß der Zufriedenheit der Bevölkerung mit dem politischen System bestimmen. Dieser theoretische Ansatz widerspricht der These von der kulturellen Fundierung demokratischer Stabilität und der daraus abgeleiteten Behauptung, daß die politische Kultur mit ihren sich nur allmählich wandelnden Eigenschaften zur stabilen Verankerung des politischen Systems beiträgt. Die hier präsentierten Ergebnisse machen deutlich, welchen Preis das politische System für die Wiedervereinigung zahlen mußte. In den neuen Bundesländern ist die Zufriedenheit mit dem politischen System der Bundesrepuklik noch immer sehr gering - und diese Unzufriedenheit macht sich auch in Westdeutschland breit. Die Zufriedenheit der Bürger im Westen mit dem politischen System ist auf den niedrigsten Stand, seitdem Daten über dieses Phänomen erhoben worden sind, gesunken. Ursachen sind die wirtschaftliche Entwicklung und die Regierungspolitik. Entgegen der kulturellen These über demokratische Stabilität ist die Zufriedenheit mitdem politischen System in Westdeutschland demzufolge nicht einfach nur gegeben: Bürger verändern ihre Einstellungen zum System aufgrund der Erfolge und Mißerfolge der Regierung und der Wirtschaft. Im Osten verhält es sich ähnlich. Die wirtschaftlichen Anstrengungen der Wiedervereinigung wie auch der Eindruck, die Bundesregierung unternehme nicht genügend, um den Lebensstandard der Ostdeutschen dem der Westdeutschen anzugleichen, hielt die Bevölkerung davon ab, sich zu dem System zu bekennen. Obwohl die meisten Ostdeutschen der Vereinigung mit der ehemaligen Bundesrepublik mittlerweile zustimmen und das bestehende politische Modell akzeptieren, ist indessen die Begeisterung dafür nur mäßig, ebenso wie für das damit verbundene Wirtschaftssystem.
Keywords: 330; Demokratie; Öffentliche Meinung; Staatsversagen; Public Choice; Deutschland; Neue Bundesländer